Scope Of Application of The Scientific Style of Speech, Features and Rules - Kasimova Muhabbatkhon Bazarovna (Zien Journals, 2024)
This article describes the unique aspects of the scientific speech style. Also, the didactic importance of mastering various methods of forming scientific information during the formation of specialists is discussed
Keywords: types of texts in scientific style; classification of genres; scientific style; method